An Investigation of the Determinants of Tax Compliance Among Yemeni Manufacturing SMEs Using the Fisher Model - Abd Obaid, Mohammed Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
Tax compliance contributesto social and economic development by reducing government fiscal deficit, debt and generating finance for infrastructure. However, there are challenges resulting from corruption and low tax compliance behaviours among SMEs which hinders generation of adequate revenues by the government. Currently, the Yemeni tax authority is focused on the increasing tax revenue generation from the large number of SMEs in the country. Therefore, this study contributes towards such effort. The objective of the study is to investigate the effect of tax fairness, peer influence and perception of corruption on tax compliance behaviour among Yemeni manufacturing SMEs. The study utilized the socio-psychological theory,primarilythe Fischer model as the underlying theory. This research employs aquestionnaire survey technique. Survey instruments were circulated among 490 SMEsand the primary respondents were owner-managers of the businesses.Out of the survey questionnaire retrieved, 372werefound eligible for further analysis. The researchhypotheses weresubsequently tested utilizingthe Partial Least Squares (PLS) software and the structural equation model (SEM) technique. Findings from the study showsthat tax fairness and peer influences are positively and significantly related to SMEs tax compliance behaviour. However, perception of corruption has an insignificant impact on tax compliance among Yemeni SMEs. The implication of the study is that the government and tax authority should update and provide new tax laws and policies that can ensure fairness among taxpayers and minimize corruption among government officials.There is need to create more awareness among SMEs on the importance of paying tax to the government. Based on findings from this study, if these measures are implemented, it is hoped that SMEs’ owner-managers would improve their tax compliance.